Activated protein C (APC) can increase bone anabolism via a protease‐activated receptor (PAR)1/2 dependent mechanism. Issue 12 (15th September 2014) - Shen, Kaitlin; Murphy, Ciara M.; Chan, Ben; Kolind, Mille; Cheng, Tegan L.; Mikulec, Kathy; Peacock, Lauren; Xue, Meilang; Park, Sang‐Youel; Little, David G.; Jackson, Chris J.; Schindeler, Aaron
ABSTRACT Activated Protein C (APC) is an anticoagulant with strong cytoprotective properties that has been shown to promote wound healing. In this study APC was investigated for its potential orthopedic application using a Bone Morphogenetic Protein 2 (rhBMP‐2) induced ectopic bone formation model. Local co‐administration of 10 µg rhBMP‐2 with 10 µg or 25 µg APC increased bone volume at 3 weeks by 32% (N.S.) and 74% (p < 0.01) compared to rhBMP‐2 alone. This was associated with a significant increase in CD31+ and TRAP+ cells in tissue sections of ectopic bone, consistent with enhanced vascularity and bone turnover. The actions of APC are largely mediated by its receptors endothelial protein C receptor (EPCR) and protease‐activated receptors (PARs). Cultured pre‐osteoblasts and bone nodule tissue sections were shown to express PAR1/2 and EPCR. When pre‐osteoblasts were treated with APC, cell viability and phosphorylation of ERK1/2, Akt, and p38 were increased. Inhibition with PAR1 and sometimes PAR2 antagonists, but not with EPCR blocking antibodies, ameliorated the effects of APC on cell viability and kinase phosphorylation. These data indicate that APC can affect osteoblast viability and signaling, and may have in vivo applications with rhBMP‐2 for bone repair. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1549–1556, 2014.